Development and Validation of the Istiqaamah Scale for Pakistani Muslim Adults - Zafar, Jawairia (Journal of religion and health, 2025)
Istiqaamah refers to the unwavering commitment to uphold virtuous conduct and maintain consistency in patience and endurance. The present research was primarily conducted to develop a psychometrically sound measure of istiqaamah and establish its construct validity. Using an exploratory sequential mixed methods design, it comprised two studies. Study 1 was conducted in two phases. In Phase 1, 40 items for the Istiqaamah Scale were developed through the thematic analysis of Quranic verses, semi-structured interviews, and focus group discussions. Phase 2 involved administering this item pool to a sample of Pakistani Muslim adults (N = 346) and conducting an exploratory factor analysis (EFA) that revealed a two-factor structure (item loading 0.54-0.94) for the 13-item Istiqaamah Scale, accounting for 79.64% of the variance. The first factor measured istiqaamah in virtuous conduct (8 items), while the second measured patience and endurance (5 items). Istiqaamah had a significant positive correlation with Taqwa and Tawakkul, providing evidence for the convergent validity where emotional instability was used for the discriminant validity of the Istiqaamah Scale. Discriminant validity is established through heterotrait-monotrait correlation ratios. The HTMT correlation ratio is .01 which testifies the discriminant validity of the Istiqaamah Scale. In Study 2, confirmatory factor analysis (CFA) conducted on a sample of Muslim adults (N = 459) confirmed the 13-item, two-factor structure of the Istiqaamah Scale observed in the EFA. Overall, the Istiqammah Scale is a robust measure of istiqaamah that needs further study to develop its nomological network across global Muslim populations.